A nontoxic solvent based sol–gel Cu2ZnSnS4 thin film for high efficiency and scalable low-cost photovoltaic cells1. Issue 29 (7th August 2015) - Tunuguntla, Venkatesh; Chen, Wei-Chao; Shih, Pei-Hsuan; Shown, Indrajit; Lin, Yi-Rung; Hwang, Jih-Shang; Lee, Chih-Hao; Chen, Li-Chyong; Chen, Kuei-Hsien
<x xml:space="preserve">Abstract</x> We are introducing a non-toxic solvent, 1, 3-dimethyl-2-Imadazolidinone, for the preparation of CZTS ink and demonstrated 5.67% efficiency CZTS device.